Prevalence of mental health problems among children with long COVID: A systematic review and meta-analysis - Mat Hassan, Nurulhuda; Salim, Hani Syahida; Amaran, Safiya; Yunus, Nurul Izza; Yusof, Nurul Azreen; Daud, Norwati; Fry, Deborah (Public Library of Science, 2023)
Introduction The number of children with mental health problems has more than doubled since the COVID-19 pandemic. However, the effect of long Covid on children’s mental health is still debatable. Recognising long Covid as a risk factor for mental health problems in children will increase awareness and screening for mental health problems following COVID-19 infection, resulting in earlier intervention and lower morbidity. Therefore, this study aimed to determine the proportion of mental health problems post-COVID-19 infection in children and adolescents, and to compare them with the population with no previous COVID-19 infection. Methodology A systematic search was done in seven databases using pre-defined search terms. Cross-sectional, cohort and interventional studies reporting the proportion of mental health problems among children with long COVID in the English language from 2019 to May 2022 were included. Selection of papers, extraction of data and quality assessment were done independently by two reviewers. Studies with satisfactory quality were included in meta-analysis using R and Revman software programmes. Results The initial search retrieved 1848 studies. After screening, 13 studies were included in the quality assessments. Meta-analysis showed children who had previous COVID-19 infection had more than two times higher odds of having anxiety or depression, and 14 higher odds of having appetite problems, compared to children with no previous infection. The pooled prevalence of mental health problems among the population were as follows; anxiety: 9(95 CI:1, 23), depression: 15(95 CI:0.4, 47), concentration problems: 6(95 CI: 3, 11), sleep problems: 9(95 CI:5, 13), mood swings: 13 (95CI:5, 23) and appetite loss: 5(95 CI:1, 13). However, studies were heterogenous and lack data from low- and middle-income countries. Conclusion Anxiety, depression and appetite problems were significantly increased among post-COVID-19 infected children, compared to those without a previous infection, which may be attributed to long COVID. The findings underscore the importance of screening and early intervention of children post-COVID-19 infection at one month and between three to four months.